A Case of Squamous Cell Carcinoma of Skin Subsequent to Subcutaneous Foreign Body - Anwar, P; Mubashir, S; Hassa, I; Arif, T (Nepal Journal of Dermatology, Venereology & Leprology, 2016)
Squamous cell carcinoma (SCC) of the skin is one of the most common non melanoma skin cancers (NMSC), along with basal cell carcinoma (BCC). Besides ultraviolet radiation, the role of exposure to industrial agents, ionizing radiation and areas of chronic inflammation is associated with the development of SCC. SCC may also be associated with foreign bodies. We report a rare case of cutaneous SCC in an elderly Kashmiri female, developing subsequent to subcutaneous non metallic foreign body, which was successfully excised with negative margins, and transposition flap closure. DOI: http://dx.doi.org/10.3126/njdvl.v12i1.10604 Nepal Journal of Dermatology, Venereology & Leprology Vol.12(1) 2014 pp.53-55 <!–[endif] –>